Customer satisfaction from private utility companies: An explanatory study - Eleni-Plousia Kosteroglou; Georgios Theriou; Dimitrios Chatzoudes (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2016)
Purpose -The present study examines the factors that have an impact on 'customer satisfaction' in the context of private utility companies. The main purpose of the study is accomplished through the development and the empirical testing of a conceptual framework (research model). The proposed framework includes six dimensions (research factors): (a) tangibles, (b) reliability, (c) responsiveness, (d) assurance, (e) empathy, and (f) customer satisfaction. Design/methodology/approach - The present study adopted the SERVQUAL approach (model), only after analytically testing its suitability for use within the investigated area. In that direction, the focus group methodology was used. Finally, the proposed conceptual framework was tested on a random sample of gas consumers residing in the area of Thessaloniki, Greece. The final sample consisted of 437 adult consumers. The reliability and the validity of the questionnaire were thoroughly examined. Empirical data were analysed using the 'Structural Equation Modelling' (SEM) technique. The present study is empirical, explanatory, deductive and, mainly, quantitative. Findings - Empirical results indicate that 'reliability' has the highest impact on 'customer satisfaction', while 'empathy' has no impact at all. More specifically, the impact of 'reliability' on 'customer satisfaction' is indirect, mediated through three other dimensions of the conceptual framework (namely, 'tangibles', 'responsiveness' and 'empathy'). Research limitations/implications - A limitation stemming from the implemented methodology is the use of self-reported scales for the measurement of the six research factors. Moreover, the paper lacks a longitudinal approach. Finally, the empirical research (survey) is focused on one organisation and, therefore, offers relatively limited generalizability. Originality/value - Very few studies have utilised the SERVQUAL approach in the context of an explanatory research. This approach offers a unique understanding of the relationship that exist between its five dimensions (factors) (tangibles, reliability, responsiveness, assurance, empathy). Such an approach has very rarely been attempted in the relevant literature.
Keywords: D12; L80; L94; 330; Customer satisfaction; Utility companies; SERVQUAL; Empirical study; Structural Equation Modelling